(untitled) (University Heart Journal, 2009)
Cardiac arrhythmias often present to family physicians with diverse clinical manifestations. This retrospective observational study was carried out in a private cardiology clinic in Dhaka from July 2004 to December 2008. A total of 1257 patients were referred from family physicians in the locality. 75 (5.96%) patients were diagnosed as having cardiac arrhythmia by ECG. Various types of atrial arrhythmias are more common than ventricular arrhythmias (60% vs 40%). Atrial fibrillation (N=18) and PVC (N=17) are the 2 commonest arrhythmias found in this study. This study identifies the clinical presentation, possible aetiology and management of patients having cardiac arrhythmias. Palpitation (46.66%) and asymptomatic ECG changes (34.66%) were the 2 most common reasons for referral. Most of the patients could be managed on a out-patient basis. Most arrhythmias like 1st degree heart block, PAC & isolated PVC, RBBB, Sinus bradycardia were asymptomatic & did not need any further treatment except assurance & anxiolytics. Other arrhythmias like atrial fibrillation, LBBB, bifascicular or advanced heart block, SSS & SVT needed further evaluation. This article particularly focuses on the general approach of family physicians while dealing with patients with cardiac arrhythmias. Key words: cardiac arrhythmias, family medicine practice doi: 10.3329/uhj.v5i1.3435 University Heart Journal Vol. 5, No. 1, January 2009 17-19